Q: 3b - 2 equals 7b plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7

If b = -1.5 then -4.5 -2 = -10.5 + 4, which is true.

Add 2 to each side: 3b = 7b + 6 Subtract 7b from each side: -4b = 6 Divide each side by 4: -b = 1.5 Change sign: b = -1.5

2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================

If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified

Related questions

26 = 3b - 2 - 7b 28 = -4b b = -7

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7

If b = -1.5 then -4.5 -2 = -10.5 + 4, which is true.

Add 2 to each side: 3b = 7b + 6 Subtract 7b from each side: -4b = 6 Divide each side by 4: -b = 1.5 Change sign: b = -1.5

2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================

3b + 6 = 12 3b = 6 b = 2

If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified

b^2 - 7b + 12 = b^2 - 4b - 3b + 12 = b(b -4) -3(b - 4) = (b - 3)(b - 4)

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

a+b+2+3=5+a+b

20+3b = 20 + 3(-6) = 20-18 = 2